Estudo de fônons em nanotubos de carbono e dissulfeto de molibdênio: efeito do acoplamento entre camadas - Alencar, Rafael Silva (2016)
In this work we present the studies on Double (DWCNTs) and Triple Wall Carbon Nanotubes, on molybdenum disulfide in the bulk form and on few layer of MoS_2 under hydrostatic high pressure conditions. Theoretical calculations were performed in collaboration to support the experimental results. For the DWCNTs samples, changes in the G-band frequency vs. pressure plot and the disappearance of the radial breathing modes (RBM) between 2 GPa and 5 GPa indicate the beginning and ending of the radial collapse of the nanotubes. Theoretical calculations based on Density-Functional Tight-Binding (DFTB) shown that the collapse pressure (P_c) for DWCNTs follows a d^{-3}_{in} law, in excellent agreement with the experimental results. The P_c dependence on number of tube-walls and on the inter-wall distance is also investigated. For the TWCNTs samples, pressure screening effects are observed for the innermost tubes of TWCNTs similar to what has been already found for DWCNTs. However, using the RBM pressure coefficients in conjunction with the histogram of the diameter distribution, we were able to separate the RBM Raman contribution related to the intermediate tubes of TWCNTs from that related to the inner tubes of DWCNTs. By combining Raman spectroscopy and high pressure measurements, it was possible to identify these two categories of inner tubes even if the two tubes exhibit the same diameters, since their pressure response is different. Furthermore, it was possible to observe similar RBM profiles of the innermost tubes of TWCNTs using different resonance laser energies but also under different pressure conditions. This is attributed to changes in the electronic transition energies caused by small pressure-induced deformations. Theoretical calculations based on ab initio were performed for support the experimental results. By using Raman spectroscopy, it was possible to estimate the displacement of the optical energy levels with pressure. For the exfoliated MoS_2 samples, we studied the effect of the stacking on the E^1_{2g} and A_{1g} vibrational modes at high pressures. New components for both modes were observed with increasing pressure. It was also observed that the pressure coefficient of the E^1_{2g} mode decreases exponentially with MoS_2 thickness is increased, differently of the A_{1g} mode and the new components, which do not present a significant dependence on the variation of the number of layers. These results were attributed to deformations in the MoS_2 structure induced by a biaxial strain (dependent on the number of layers), resulting from the deformation of the SiO_2 substrate. Such adhesion decreases with the increasing of the MoS_2 thickness due to the increasing on the unbinding regions between MoS_2 and SiO_2. As result, a higher pressure is needed to improve the adhesion and consequently, a higher pressure is required to achieve the biaxial strain. For the MoS_2 microcrystalline powder, except for the B_{1u}, E^2_{2g}, E_{1g}, E^1_{2g} and A_{1g} modes, the behavior of all other modes was studied for the first time in high pressure conditions. For all modes, a linear variation of the Raman frequency and positive pressure coefficient was observed. Moreover, the differences in the behavior of the intensity profiles of the A_{1g}, 2LA(M) and A_{2u} modes in resonance and off-resonance were attributed to variations in the energy of direct optical transitions induced by pressure.